2005
DOI: 10.1530/eje.1.01920
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of androgen replacement influences bone density response to testosterone in androgen-deficient men

Abstract: Objective: Androgen deficiency (AD) leads to bone loss and contributes to osteoporotic fractures in men. Although low bone mineral density (BMD) in AD men is improved by testosterone replacement, the responses vary between individuals but the determinants of this variability are not well defined. Design and methods: Retrospective review of dual energy X-ray absorptiometry (DEXA) of the lumbar spine and proximal femur in men with established AD requiring regular androgen replacement therapy (ART). After a DEXA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Studies on hypogonadal men (other than KS) have shown a significant effect of testosterone treatment on BMD in both hip and spine during 36 months [33] and 42 months [34] of testosterone treatment, respectively. An Australian study showed that adequacy of testosterone supplementation determined BMD gain in hypogonadal men [35]. We found that KS were taller and more obese as seen from the higher BMI.…”
Section: Discussionmentioning
confidence: 49%
“…Studies on hypogonadal men (other than KS) have shown a significant effect of testosterone treatment on BMD in both hip and spine during 36 months [33] and 42 months [34] of testosterone treatment, respectively. An Australian study showed that adequacy of testosterone supplementation determined BMD gain in hypogonadal men [35]. We found that KS were taller and more obese as seen from the higher BMI.…”
Section: Discussionmentioning
confidence: 49%
“…These features, together with the long interval between injections, contribute to the high patient acceptability and continuation rates compared with other shorteracting forms of T replacement therapy. Previous underreporting [8][9][10][12][13][14] or underestimation [11,14] of TU-related injection pain may be an unrecognized limitation for the most effective clinical uses of TU, which assume a high level of therapeutic compliance for optimal, life-long androgen replacement therapy [45], or for a well-accepted TU-based combination of hormonal male contraceptive regimens [46].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of trials have demonstrated a positive effect of testosterone treatment on bone mineral density (Katznelson et al 1996;Behre et al 1997;Leifke et al 1998;Snyder et al 2000;Zacharin et al 2003;Wang, Cunningham et al 2004;Aminorroaya et al 2005;Benito et al 2005) and bone architecture (Benito et al 2005). These effects are often more impressive in longer trials, which have shown that adequate replacement will lead to near normal bone density but that the full effects may take two years or more (Snyder et al 2000;Wang, Cunningham et al 2004;Aminorroaya et al 2005).…”
Section: Effects On Bone and Osteoporosismentioning
confidence: 99%
“…These effects are often more impressive in longer trials, which have shown that adequate replacement will lead to near normal bone density but that the full effects may take two years or more (Snyder et al 2000;Wang, Cunningham et al 2004;Aminorroaya et al 2005). Three randomized placebo-controlled trials of testosterone treatment in aging males have been conducted (Snyder et al 1999;Kenny et al 2001;Amory et al 2004).…”
Section: Effects On Bone and Osteoporosismentioning
confidence: 99%